Assessing intercultural understanding: the facts about strangers. Issue 5 (29th July 2022) - McCandless, Trevor; Fox, Brandi; Moss, Julianne; Chandir, Harsha
ABSTRACT: The aim of this paper is to present a schema that maps the terrain of intercultural assessment strategies. This schema is based upon Haraway's semiotic square and has two dimensions. The first considers how distant or near the cultural Other is understood to be – whether they are perceived a stranger or a neighbour . The second considers whether the student is encouraged to see the cultural Other as an object about whom one learns facts, or if student and the cultural Other are expected to interact as a means to transforming their mutually interrelated lives. We argue that this mapping helps illuminate the benefits and shortcomings of various assessment strategies, highlighting the underlying curricular assumptions and objectives of these assessment strategies. This paper argues that curricular and assessment models that treat cultural Others as neighbours engaged in joint transformative change should increasingly be the focus of intercultural learning and assessment strategies. A review of extant literature found that school systems, international and transnational curriculum bodies, and some for-profit companies provide a wide range of models for assessing student intercultural awareness, understanding and componence. These models differ so significantly that the term "intercultural" may appear a floating signifier. However, the benefit of our schema is in classifying these models by focusing on the forms of intercultural interactions they anticipate.